Citizens of Zagreb on energy : knowledge, attitudes, and behavior : results of a Survey - Čaldarović, Ognjen (2009)
The lecture discusses the major results of a survey performed on a sample of Zagreb population concerning their attitudes and habits concerning the use of renewable energy resources.